'How do you get the courage to stand up?' Teachers' constructions of activism in response to education policy reform. Issue 4 (4th July 2021) - Warren, Amber; Ward, Natalia
ABSTRACT: This study explores how six teachers worked up becoming and being activists in response to education reforms in the southeastern US. The reforms, which involved increasing student testing and implementing high-stakes teacher evaluations, were enacted following the authorization of the Every Student Succeeds Act, federal legislation governing elementary and secondary education. Discourse analysis of interview data demonstrates how engaging in activism was constructed and positioned by teachers in response to these policy changes. We describe two interrelated patterns: (1) characterizing activism as requiring 'professionalism' on the part of the teacher-activist; and (2) justifying their actions by contrasting versions of activism in the media with their own activism, which they aligned with commonly accepted category-bound activities tied to 'doing' being a teacher. Findings shed light on the nuanced negotiation of educators' roles as teacher-activists within the current policy context and the complicated nature of framing professionalism and activism for public audiences.